The transparency of the Infinite: on a possible Phenomenology of art in Jan Patočka’s thought (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In the present work we try to provide some concise remarks concerning the possibility of rebuilding an “aesthetical theory” from the indications framed in this respect by the Czech philosopher Jan Patočka. On the basis of his distinction between “traditional art” and “modern art”, that is, between the art conceived as a “sign” and the art intended in an authonomous manner, we try to show the way in which Patočka places the essence of art in the act of revealing the hidden side of reality. It would be that extraordinary dimension of the things that is revealed in its pure and simple appearing: beyond all utilitarian or pragmatic gaze.
Keywords: Patočka; aesthetical phenomenology; appearing; totality